Adaptation of on-line rapid sampling microdialysis to monitor human intestinal ischaemia - Corcoles,EP; Deeb,S; Hanna,G; Boutelle,MG; Darzi,A (Jurnal Teknologi Sciences and Engineering, 2011)
Intestinal ischaemia or poor perfusion of the gastrointestinal tract is a major cause of post-operative mortality in abdominal surgery. Currently diagnosis of ischaemia relies only on clinical symptoms. Thus, monitoring bowel metabolism as an early marker of intestinal ischaemia is necessary. Human bowel microdialysis has been used in the past to study the metabolism of ichaemia collecting dialysate samples from the peritoneal cavity every 60 minutes. These sampling times carry a long delay for the detection of the typically rapid ischaemic event. We have previously developed a successful biosensor system to monitor neurochemicals in the human brain during surgery and in the intensive care unit The method consists of a flow injection analysis (FIA) system coupled to an enzyme based amperometric detector. The rapid sampling microdialysis monitoring system analysed electrochemically the dialysate glucose and lactate at high time resolution (typically 30 second sampling). Adaptation of the analytical assay system for on-line microdialysis monitoring of human bowel was performed and validated for in vivo procedures. Optimum membranes loading ratios were found to be 1:0.5 GOx:HRP and 2:0.5 LOx:HRP. The ischemic range was found to be 15μM-400μM, 40μM-6mM for glucose and lactate, respectively. The calibration method for these monitorings was concluded with a range from 250 μM to 6 mM. © Universiti Teknologi Malaysia.